The role of comorbidities in patients' hypertension self-management. (June 2014) - Fix, Gemmae M; Cohn, Ellen S; Solomon, Jeffrey L; Cortés, Dharma E; Mueller, Nora; Kressin, Nancy R; Borzecki, Ann; Katz, Lois A; Bokhour, Barbara G
Objective: We sought to understand barriers to hypertension self-management in patients with hypertension and comorbidities. Methods: We conducted semi-structured, qualitative interviews with 48 patients with uncontrolled hypertension and at least one comorbidity to learn about beliefs and behaviors that might affect hypertension self-management. Using a grounded theory strategy, we analyzed interview transcripts detailing patients' hypertension self-management behaviors vis-à-vis a framework including Explanatory Models —a patient's understanding of the pathophysiology, cause, course, treatment, and severity of an illness, such as hypertension. Results: We identified four factors that interfered with hypertension self-management. (1) Interdependence: Participants saw hypertension as interconnected to their comorbidities and subsequently had difficulty separating information about their illnesses. (2) Low priority: Compared to other conditions, participants assigned hypertension a lower priority. (3) Conflicts: Participants struggled with conflicts between hypertension self-management practices and those for comorbidities. (4) Managing multiple medications: Polypharmacy led to patients' confusion and concern about taking medications as prescribed. Discussion: Participants did not experience hypertension as a discreet clinical condition; rather, they self-managed hypertension concurrently with other conditions, leading to a breakdown in hypertension self-management. We provide strategies to address each of the four barriers to better equip providers in addressing their clinically salient concerns.